DEGRADASI BAHAN ORGANIK LIMBAH CAIR NANAS OLEH BAKTERI INDIGEN - Sutanto, Agus (El-Hayah : Jurnal Biologi, 2011)
Pineapple Liquid Waste has high organic material  and still unfulfilled required quality standard. Processing occurred at the waste processing installation with pond system (Lagoon) required a wide space and keep long time so that less efficient. Based on this problem, it needs an environmentally sound waste management by utilizing bioprocess technology using indigenous bacteria’s ability in degrading organic pollutant called Bioremediation. The objective of this research was to get isolated indigenous bacteria, enables to decrease organic material. It was divided into four stages. First, performed characteristic observation of isolated bacteria that potentially decrease organic material, secondly decomposition capability test in vitro, and thirdly scale bioremediation test pilot plan, fourthly bioremediation test in ex situ at the microbiology laboratory of Malang State University. Data were analyzed by Varian analysis to test the presence or absence of differences and regression test to analyze the link between variables. First phase result: 15 isolated indigenous bacteria.. Potential consortia bacteria consisting of more effective 4 species, indicated by 4 consortia bacteria decreased BOD in 6 days. Starter bacteria with a consortia K1’s combination (ABCD), Volume: 5% (v/v) and 6 days were the most effective incubation time in decreasing BOD. Second phase result: 1) A significant link among the number of bacteria, a. Bacillus cereus, b. Acinetobacter baumanni, c.Bacillus subtilis, d. Pseudomonas pseudomallei and not abcd against organic material with contribution of 72,7% and negatively correlated, 2) Media treatment and incubation time gave distinctive outcome against organic material,  3) there was a link between organic material organic acid concentration decrease would decrease BOD  at scale bioremediation test Pilot plan, and ex situ scale. Threshold BOD achievement limit value on 10th day (75) quality standard: 75. In accordance with ministry decree LH No. 05 year 2007 industrial wastewater quality standard, suggested to industry to use this study in processing its waste.Keywords: organic material, isolated indigenous bacteria, pineapple liquid waste.